2012
DOI: 10.1248/bpb.b12-00072
|View full text |Cite
|
Sign up to set email alerts
|

Benzofuran Derivatives Inhibit 11β-Hydroxysteroid Dehydrogenase Type 1 Activity in Rat Adipose Tissue

Abstract: Excess glucocorticoids promote visceral obesity and insulin resistance. The main regulator of intracellular glucocorticoid levels are 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1), which converts inactive glucocorticoid into bioactive glucocorticoid such as cortisol in humans and corticosterone in rodents; therefore, the inhibition of 11β-HSD1 has considerable therapeutic potential for metabolic diseases including obesity and diabetes. Benzofuran is a key structure in many biologically active compounds su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…In addition, these data showed that resveratrol does not inhibit G6PT, which is located in the membrane of the endoplasmic reticulum and supplies G6P to the lumen (Chou et al 2002). Further, these results were consistent with features of previous studies, indicating that no inhibition of H6PD by E 2 and 2-arylbenzofuran derivatives was observed (Tagawa et al 2009, Kiyonaga et al 2012. These characteristic properties might also be because of the typical structure of the spatial configuration of the two hydroxyl groups as observed in resveratrol, E 2 , or 2-arylbenzofuran derivatives.…”
Section: Figuresupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, these data showed that resveratrol does not inhibit G6PT, which is located in the membrane of the endoplasmic reticulum and supplies G6P to the lumen (Chou et al 2002). Further, these results were consistent with features of previous studies, indicating that no inhibition of H6PD by E 2 and 2-arylbenzofuran derivatives was observed (Tagawa et al 2009, Kiyonaga et al 2012. These characteristic properties might also be because of the typical structure of the spatial configuration of the two hydroxyl groups as observed in resveratrol, E 2 , or 2-arylbenzofuran derivatives.…”
Section: Figuresupporting
confidence: 91%
“…1C) and 2-(4-hydroxyphenyl)-6-benzofuranol (Fig. 1D), having a distance of w12 Å between the two hydroxyl groups in their molecules, inhibited 11b-HSD1 activity without 11b-HSD2 inhibition (Kiyonaga et al 2012). Therefore, two hydroxyl groups at the C-4 0 and C-3 or C-5 positions with the same distance (w12 Å ) in resveratrol may be crucial for the selective inhibition of 11b-HSD1.…”
Section: Figurementioning
confidence: 96%
See 2 more Smart Citations
“…6.1, and found to be about 12-13 Å (13.48 Å, Fig. 1A), is approximately the same as the corresponding distance in 17b-estradiol (12.12 Å) [22]. These findings prompted us to examine whether genistein has inhibitory effects on 11b-HSD1 and H6PD activities.…”
Section: Introductionmentioning
confidence: 56%